PENGARUH NON PERFORMING LOAN, BIAYA OPERASI PADA PENDAPATAN OPERASI, DAN NET INTEREST MARGIN TERHADAP PERTUMBUHAN LABA (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2007-2011) - Nayoan, Fera (Katalogis, 2018)
This research aims to analyze the effects of non perfoming loan, operation cost of operation income and net interest margin on profit growth. Data have been collected from financial report of general banking companies which are registered at Indonesia Stock Exchange within period of five years (2007-2011). Sample of this research cover 10 general banks that have been selected using pourposive sampling technique. This study employs multiple linear regression to test proposal hypotheses. The results show that non performing loan, operation cost of operation income and net interest margin simultaneously perform significant effects on profit growth. Partially, non performing loan, and operation cost of operation income perform negative and significant effects on profit growth, meanwhile net interest margin performs positive and significant effect on profit growth. Based on the result of multiple linear regression, it indicates that profit growth is affected by 56,8% of those three variables, and 43,2% is affected by other factors which are not investigated in this research.